Establishment of A Reproductive Health Care Carader in Integrated Service Post (Posyandu) Youth Village Penyengat Olak Muaro Jambi District - Ruwayda Ruwayda; Dewi Nopiska Lilis; M Dody Izhar (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
At the posyandu for youth, the IEC includes providing information about adolescent reproductive organs, puberty, the process of pregnancy, menstruation, family planning, sexually transmitted diseases, gender and maturity of marriage age. HIV / AIDS includes providing information about transmission, prevention and symptoms. Based on data from the Health Office of Muaro Jambi Regency, in the area of ??Puskesmas Penyengat Olak, the target number of adolescents aged 10-18 years is 1,959 males and 1,903 females. This large number is an opportunity to form a youth posyandu. Community service activities will be carried out in Penyengat Olak Village, Muaro Jambi Regency. This community service aims to increase the capacity of youth as cadres of the village post at Penyengat Olak district. Muaro Jambi. Target adolescents aged 10-18 years who are in the area of ??olak stinger health centers. There are activities in the form of advocacy to puskesmas and the community in establishing youth Posyandu, recruiting cadres and holding youth Posyandu cadres training, implementing youth Posyandu formation in stinging olak villages. The output of community service activities is the formation of cadres to care for reproductive health in pilot youth Posyandu for the work area of ??the Pengegat Olak Community Health Center in Muaro Jambi Regency. olak stinger. Through this training activity it is very important to increase the coverage of adolescent reproductive health services and it is hoped that the support of the puskesmas and village officials is expected.